A READING OF THE EVENT IN THE BLACK SWAN DIRECTED BY DARREN ARONOFSKY - Marinho, Cíntia Morais (Laboratório Editorial FCL-UNESP, 2012)
Using the theoretical concepts proposed by Zilberberg about the notion of event, this paper aims to analyze two short scenes from the movie Black Swan (2010) directed by Darren Aronofsky. In the narrative, Nina is part of a big American ballet company and she wants to get the lead role in the next season. The two selected episodes synthesize events that reverse the direction of the narrative game, making room for the regency of the concessive in the chain of events that constitutes the subject’s search. Therefore, they are ideal for putting into practice the use of recent developments arising from the tensile Semiotics.